2019
DOI: 10.1149/2.1191906jes
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted ALD of LiPO(N) for Solid State Batteries

Abstract: All solid state 3D batteries are pursued for their increased safety and high power capabilities. At present conformal coating of the solid electrolyte remains one of the key hurdles for the implementation of such devices. In the present work we investigate atomic layer deposition (ALD) as means of conformal deposition of lithium phosphate (Li 3 PO 4 ) and nitrogen doped lithium phosphates (LiPON). These processes are characterized here to obtain the highest possible Li-ion conductivity. Li 3 PO 4 is shown to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
2
31
1
Order By: Relevance
“…In concert with this effect, it has also been observed that the conductivity of LiPON films also benefits from the introduction of excess lithium during processing, which presumably increases the concentration of interstitial lithium available for conduction (Xiao et al, 2018). Interestingly, these effects can be realized with the obvious commensurate changes in precursor (i.e., sputtering target) chemistry, but also by changing the processing atmosphere and sputtering parameters (Xiao et al, 2018;Put et al, 2019). With so many possible factors contributing to the conductivity of LiPON, it is perhaps unsurprising that the measured conductivities of LiPON of the same nominal composition can vary up to three orders of magnitude when different processing techniques are employed and the data are collated (Famprikis et al, 2019b).…”
Section: Structure-property Relationships In Liponmentioning
confidence: 99%
See 1 more Smart Citation
“…In concert with this effect, it has also been observed that the conductivity of LiPON films also benefits from the introduction of excess lithium during processing, which presumably increases the concentration of interstitial lithium available for conduction (Xiao et al, 2018). Interestingly, these effects can be realized with the obvious commensurate changes in precursor (i.e., sputtering target) chemistry, but also by changing the processing atmosphere and sputtering parameters (Xiao et al, 2018;Put et al, 2019). With so many possible factors contributing to the conductivity of LiPON, it is perhaps unsurprising that the measured conductivities of LiPON of the same nominal composition can vary up to three orders of magnitude when different processing techniques are employed and the data are collated (Famprikis et al, 2019b).…”
Section: Structure-property Relationships In Liponmentioning
confidence: 99%
“…Further, the volumetric capacity is often reported rather than specific gravimetric capacity (as is typical in bulk ASSBs) due to the unique configurations of these microbatteries. The presented batteries demonstrate the ability to sputter the cathodes as well, which include LCO, LTO (Put et al, 2019), and LNMO (Yada et al, 2014) thin films. These batteries are typically supported by hard substrates such as SiO 2 or flexible substrates (Song et al, 2010) to impart flexibility to the thin film battery as a whole.…”
Section: Stability Of Liponmentioning
confidence: 99%
“…In later work it was shown that the N-content in the films can be controlled by the plasma power, in a similar fashion to the RF-sputter depositions. [86] In addition, plasma enables lower deposition temperatures (down to 100 °C) and reduces the amount of impurities in the film. [84,86] This might open the way for LiPON protectvive coatings on metallic lithium.…”
Section: Conformal Solid-state Electrolytesmentioning
confidence: 99%
“…[86] In addition, plasma enables lower deposition temperatures (down to 100 °C) and reduces the amount of impurities in the film. [84,86] This might open the way for LiPON protectvive coatings on metallic lithium. However, the need for a plasma step makes it less straightforward to obtain conformal films.…”
Section: Conformal Solid-state Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation